Analysis of Confidence Levels of Rich Slalom Rowing Athletes Hours - Rhama Nurwansyah Sumarsono (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to assess the level of confidence of athletes such as fast current slalom. This study uses the ex-post facto methodology. Purposive sampling was used to select 12 athletes consisting of 7 males and 5 females. The questionnaire used for data collection was given to rowing athletes such as heavy current slaloms. The self-confidence instrument is a method used to collect research data. The result is, of the 5 male athletes, the